CIVILIZATIONAL TRANSITION AND SPIRITUAL INTELLIGENCE: A SYSTEMIC ANALYSIS OF CONTEMPORARY SOCIO-STRUCTURAL CHALLENGES - Ribeiro, José Genilson Alves (Seven Editora, 2026)
The article proposes that humanity is undergoing a civilizational transition in which geopolitical and health crises act as catalysts for overcoming an anthropocentric and unequal model. It is argued that exacerbated individualism and predatory exploitation have reached their limits, revealing the collapse of structures that prioritize competition over cooperation. The solution lies in Spiritual Intelligence (SQ), a capacity that enables individuals to reframe suffering and act as agents of ethical transformation. From a systemic perspective, society is described as an interdependent organism; therefore, environmental balance and social justice are inseparable from inner reform. The text emphasizes the ethics of otherness and humility as pillars of a new paradigm, urging conduct guided by sustainability and compassion to ensure survival in the Anthropocene and collective moral evolution.